FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH KOTA PAYAKUMBUH DALAM MEWUJUDKAN CITY OF RANDANG TAHUN 2019 DI PROVINSI RIAU TAHUN 2018-2019 - Wilda Rafdiani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The regional autonomy implemented causes the local government  have the opportunity to regulate its respective regions by being obliged to develop its regional potential in accordance with regional conditions, local wisdom, regional potential and regional superior potential to improve the welfare of the community. Randang is familiar to the national and international community. Randang is a typical food from Minangkabau area. Payakumbuh city is one of the cities in West Sumatra Province which has many IKM Randang. With the potential of Randang, the Government of Payakumbuh City made its city icon as the City of Randang. The seriousness of the government towards Payakumbuh City of Randang with the form of IKM Randang Center and UPTD P3Randang. With the issue of the mayor's regulation on the establishment of UPTD P3R makes UPTD as the driver and implementer in the development of randang.This research aims to find out the factors that influence implementation of Payakumbuh City Government policy in realizing the City of Randang which is seen using the theory of Edward III. The research site is located in Payakumbuh City at Payakumbuh Town Hall Office, Payakumbuh City Labor and Industry Office and UPTD (P3R) Center IKM Randang Kota Payakumbuh. This research uses a qualitative approach. This type of research is descriptive. Data is collected through informants purposively. Data collection techniques uses interviews and documentation.The results of this study are Implications of Payakumbuh Local Government Policy in Realizing Payakumbuh City Of Randang Year 2019, especially Mayor's Regulation Number 30 year 2019 has not been running optimally. Of the four factors based on Edward III's theory, that the inhibitory factors are communication factors such as lack of information in coaching and mentoring for IKM followed by the lack of number of UPTD Employees, factors such as lack of facilities and infrastructure and lack of cooperative human resources in conducting marketing activities. Keywords : IKM, Payakumbuh City of Randang, Policy Implementation, UPTD P3R, Edward III